2012
DOI: 10.1186/1751-0147-54-48
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole resistance of sheep nematodes in Norway confirmed through controlled efficacy test

Abstract: BackgroundResistance against benzimidazoles (BZ) has recently been detected in Norwegian sheep flocks through a large scale prevalence survey based on the faecal egg count reduction test (FECRT). The use of this test in combination with bulk larval culture only gives an indication of which gastrointestinal nematodes genera that are involved and these results have to be confirmed by a controlled efficacy test (CET) to get accurate information about resistant nematodes populations at species level. A CET was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Recent research has shown that there is a high treatment frequency with anthelmintic drugs in sheep lambs in Norway, particularly in coastal areas (1), which may be responsible for the development of anthelmintic resistance (2,3). Strategies to prevent helminth infections are needed to reduce treatments with anthelmintics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that there is a high treatment frequency with anthelmintic drugs in sheep lambs in Norway, particularly in coastal areas (1), which may be responsible for the development of anthelmintic resistance (2,3). Strategies to prevent helminth infections are needed to reduce treatments with anthelmintics.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on the occurrence and prevalence of AR for GINs in Norway. BZ resistance has been detected in Haemonchus contortus in several sheep flocks in Norway by the fecal egg count reduction test (FECRT) [13], and later confirmed by experimental infections and controlled efficacy testing (CET) [16]. Resistance against ML has also been detected in H. contortus in one sheep flock in Norway by FECRT [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, data concerning drenching routines was limited in the present study. Anthelmintic resistance may also be a contributing factor, as it has previously been detected in T. circumcincta from sheep in Norway, but so far not in Trichostrongylus [29,30]. Detection of Trichostrongylus was performed at the genus-level, and therefore it is likely that several species (i.e., T. colubriformis, T. vitrinus, T. axei) contributed to the category of Trichostrongylus, as all these species have been identified previously in Norwegian sheep flocks [8,38].…”
Section: Discussionmentioning
confidence: 93%
“…This may have influenced sheep density during grazing, which, in turn, could increase the infection pressure of pasture parasites. Another potential factor is development of AR, which was first reported in 2012 [29,30]. Nevertheless, it should be underlined that these studies are cross sectional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation